Changes during storage in volatile compounds of butter produced using cow, sheep or goat’s milk - Hayaloğlu, Ali̇ Adnan; Çakmakçi, Songül; Tahmas-Kahyaoglu, Deren (Elsevier BV, 2022)
In this study, a total of 96 volatile flavour compounds were identified in butter samples, including 12 aldehydes, 10 ketones, 22 esters, 24 alcohols, 11 acids, 4 sulphur compounds, and 13 terpenes. Aldehyde and ketone compounds were most common in cow milk butter; acid, and terpene were most common in sheep butter; and ester, alcohol, and sulphur compounds were most common in goat butter. 2,3-butanedione (diacetyl) is accepted as the key compound for the typical butter flavour, and was detected only in cow butter and decreased during storage. However, 2,3-butanediol, which is one of the main compounds produced by lactic acid bacteria with pyruvate catabolism, was determined in all kinds of butter.